2017
DOI: 10.1016/j.fertnstert.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Conception by means of in vitro fertilization is not associated with maternal depressive symptoms during pregnancy or postpartum

Abstract: Despite the psychologic distress characterizing subfertility and its treatment, conception by means of IVF is not associated with maternal depressive symptoms during pregnancy or postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…Despite psychological stress and hormonal stimulation treatments that may expose patients with infertility or subfertility to stress disorders such as depression and anxiety [2], a higher risk of perinatal depressive symptoms has been indicated by one study [17]; our study confirmed in an Italian population the findings of systematic reviews and meta-analyses, showing a lack of correlation between depression and MAR [23,24]. A greater risk of depression in IVF women was also not confirmed by a large Swedish longitudinal study that used the EPDS at the same timepoints as our study [19], and in an Australian study, which found more postpartum adjustment difficulties in women who had gone through several IVF attempts [35,36].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Despite psychological stress and hormonal stimulation treatments that may expose patients with infertility or subfertility to stress disorders such as depression and anxiety [2], a higher risk of perinatal depressive symptoms has been indicated by one study [17]; our study confirmed in an Italian population the findings of systematic reviews and meta-analyses, showing a lack of correlation between depression and MAR [23,24]. A greater risk of depression in IVF women was also not confirmed by a large Swedish longitudinal study that used the EPDS at the same timepoints as our study [19], and in an Australian study, which found more postpartum adjustment difficulties in women who had gone through several IVF attempts [35,36].…”
Section: Discussionsupporting
confidence: 70%
“…However, an Italian study showed slightly higher anxiety and/or depression rates in both women and partners awaiting IVF/ICSI with respect to the general population, while 18.5% of women and 7.4% of partners who had scored under the threshold at the beginning of the procedures scored above-threshold on anxiety or depression rating scales at the end of the procedures [15]. However, most studies did not find differences in depression between infertile women undergoing treatment for infertility and controls [16][17][18][19][20][21], and one found its prevalence to be reduced in IVF women compared to controls [22]. Results match the conclusions of systematic reviews and meta-analyses, which ruled out a relationship between MAR and postpartum depression [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic compilation finds out that evidences regarding general anxiety levels of the ART pregnancies are ambiguous (Gourounti 2016). A study performed in Switzerland concludes that despite the psychological distress caused by subfertility and its treatment, conception with IVF is not associated with maternal depression symptoms during pregnancy and after birth (Gambadauro et al 2017). Results of this study reflect perceptions related with the concepts of social gender and motherhood.…”
Section: Analysis Of Quantitative Studiesmentioning
confidence: 68%
“…[18,21,28,44,45] Twenty-two of the selected studies were hospital based cohort studies, [18-21, 25-28, 31-34, 36-41, 44, 46, 51, 52] while twelve of the selected studies were population based cohort studies. [17,22,29,30,35,42,43,45,[47][48][49][50] Fourteen studies provided data on exclusively IVF procedures, [17, 19-21, 27-29, 32, 35, 39, 43, 44, 46, 47] and six studies on ICSI procedures. [17,18,27,35,44,47] Five studies reported data on fresh embryo transfer and frozen embryo transfer.…”
Section: Study Characteristicsmentioning
confidence: 99%